2016
DOI: 10.4149/gpb_2015044
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of mesenchymal stromal cells from different tissue sources in respect to articular cartilage tissue engineering

Abstract: The main goal of this study was a comparison of biological properties of mesenchymal stromal cells (MSCs) obtained from bone marrow, adipose tissue and umbilical cord with respect to articular cartilage regeneration. MSCs were isolated and expanded in vitro up to the third passage. The kinetics of proliferation was analyzed by cell analyzer CEDEX XS and expression of selected markers was assessed by flow cytometry. The morphology was analyzed by inverted microscope and TEM. Pellet culture system and chondrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 27 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…The results showed that proliferative, differentiation, and metabolism profile of BMSC significantly decreases by age increase [53]. In the other comparative study from 2016, authors did not observe any preference in in vitro chondrogenesis among MSC derived from bone marrow, adipose tissue, and umbilical cord [54].…”
Section: In Vitro Studiesmentioning
confidence: 72%
See 1 more Smart Citation
“…The results showed that proliferative, differentiation, and metabolism profile of BMSC significantly decreases by age increase [53]. In the other comparative study from 2016, authors did not observe any preference in in vitro chondrogenesis among MSC derived from bone marrow, adipose tissue, and umbilical cord [54].…”
Section: In Vitro Studiesmentioning
confidence: 72%
“…The recent study from 2016 has emphasized that MSCs from bone marrow, adipose tissue, and umbilical cord share similar biological properties and that their chondrogenic potential does not vary [54].…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…MSCs possess several advantages as follows: 1) MSCs have extensive sources; they could be isolated from various tissues, such as bone marrow, adipose . For example, BMSCs can be obtained from bone marrow by simple gradient centrifugation and washing in phosphate‐buffered saline (PBS); meanwhile, the adipose‐tissue‐derived MSCs (ADMSCs) can be obtained from fresh lipoaspirates by rinsing with sterile PBS, digesting with 0.1% collagenase type I, and gradient centrifugation . 2) MSCs have high proliferative capacity and strong self‐renewal capacity .…”
Section: Therapeutic Cells and Growth Factorsmentioning
confidence: 99%
“…A correlation between the chondrogenic potential of MSCs and their tissue source has been suggested. BM-MSCs showed a superior chondrogenic differentiation capacity compared to MSCs from other origins [ 54 56 ]. These differences might be explained by variations in gene expression and pathway activation [ 57 ].…”
Section: In Vitro Evidence Of Chondrogenic Diffmentioning
confidence: 99%